2021
DOI: 10.18632/aging.202796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GSPT1 as prognostic biomarker and promoter of malignant colon cancer cell phenotypes via the GSK-3β/CyclinD1 pathway

Abstract: Colon cancer is the third most common malignant tumor and its mortality rate ranks fourth among all malignant tumor types. Bioinformatics analysis has shown that GSPT1 is dysregulated in colon cancer and is associated with tumor progression. However, the underlying mechanism remains unclear. To address this research gap, we examined the impact of GSPT1 on cell proliferation, apoptosis, migration, and invasion in vitro as well as tumor growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This indicates that neosubstrate expression is not in itself a reliable predictor of degradation outcome in cells and tissues. We also show that the weak degradation of GSPT1 by CC-885 correlates with a modest cell growth inhibition in HCT116 (IC50 = 0.198 μM) (Figure C, Figure S5), highlighting that more potent GSPT degraders could be used in colorectal cancer. , …”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This indicates that neosubstrate expression is not in itself a reliable predictor of degradation outcome in cells and tissues. We also show that the weak degradation of GSPT1 by CC-885 correlates with a modest cell growth inhibition in HCT116 (IC50 = 0.198 μM) (Figure C, Figure S5), highlighting that more potent GSPT degraders could be used in colorectal cancer. , …”
Section: Resultsmentioning
confidence: 76%
“…We also show that the weak degradation of GSPT1 by CC-885 correlates with a modest cell growth inhibition in HCT116 (IC50 = 0.198 μM) ( Figure 5 C, Figure S5 ), highlighting that more potent GSPT degraders could be used in colorectal cancer. 60 , 61 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the involvement of GSPT1 in translation termination and cell proliferation. Furthermore, GSPT1 silencing suppresses colony formation and cell invasion ( Hoshino et al, 1989 ; Long et al, 2021 ). Based on the decrease in expression of lncRNA NEAT1 in bald lesions, we hypothesize that the Neat1-miR-27b-3p -Gspt1 ceRNA network may be involved in AGA progression.…”
Section: Discussionmentioning
confidence: 99%
“…The GSPT1/ GSK pathway exerts tumor-promoting actions in colon cancer oncogenesis and progression. The GSPT1/GSK pathway may thus be an effective target for controlling colon cancer (26). Recently, LPP has emerged as a critical inducer of tumor cell migration, invasion and metastasis (27).…”
Section: Recognition Of Critical State Of Prostate Cancermentioning
confidence: 99%